On pain of speech : fantasies of the first order and the literary rant - Al-Kassim, Dina, 1966- (Flashpoints (Berkeley, Calif.) ;, 2010)
On Pain of Speech tracks the literary rant, an expression of provocation and resistance that imagines the power to speak in its own name where no such right is granted. Focusing on the ""politics of address, "" Dina Al-Kassim views the rant through the lens of Michel Foucault's notion of the biopolitical subject and finds that its abject address is an essential yet overlooked feature of modernism. Deftly approaching disparate fields-decadent modernism, queer studies, subjection, critical psychoanalysis, and postcolonial avant-garde-and encompassing both Euro-American and Francophone Arab.